DEMAND-SIDE MANAGEMENT FOR ENERGY PRODUCTION USING MICRO COMBINED HEAT AND POWER SYSTEM – A REVIEW - Abdulsalam, Hassan; Nuhu, Ibrahim (FUDMA JOURNAL OF SCIENCES, 2021)
World development increased dramatically ever since the Industrial Revolution, in particular after  second world war (WWII), which drove the rise of energy consumption. Thus, energy consumption in the World has been growing continuously in the past 50 years. Using micro Combined Heat and Power (mCHP) allows energy scheduling and demand-side management depending on different variables which will benefit users and suppliers. Different researches have been conducted due to increasing interest from researchers to increase and optimise the advantages of energy scheduling. In addition to the mCHP system, optimisation process also includes distributed energy sources (solar panels) with electricity storage. On the demand side, various devices with different load profiles which can be controlled over time can be considered. This study therefore, being a desktop based one, sought to review the energy demand-side management as it applies to the use of mCHP in residential settings.